Fios para a rede - cotejando conceitos de John Wesley e Edgar Morin: contribuição à educação nas instituições educacionais metodistas no Brasil, hoje. - Silva, Luiz Eduardo Prates da (2010)
In face of contemporary demands and struggling to survive against the commodification of education, confessional educational institutions, as is the case of the institutions related to the Methodist Church, seek to articulate into networks. This paper aims to highlight some specific points of John Wesley s and Edgar Morin s thought, which may allow that such networks be linked not only to the administrative and financial aspects, but have at the same time, elements of reflection carrying a load of meaning, to be found at the confluence of 'tradition', that is, the theological vision of the father of the Methodist movement, with the contemporary vision, that is, the challenges posed to education today, from Edgar Morin s paradigm of complexity viewpoint. These contributions are considered as threads weaving the fabric of the network, given that the complexus has as one of its connotations a tissue of heterogeneous constituents, inseparably bound. A net may also have other connotations, such as the "safety net", while for the fisherman, it is an instrument that ensures survival. The elements chosen as threads to weave this network are anthropology, soteriology, in the sense of social salvation, and the creation and 'new creation' in John Wesley. And still, aspects of anthropology, solidarity and the humanity s fate crisis, and education in Edgar Morin. The texture is shown based on a careful examination and comparison of these concepts/threads. Exemplifying and pointing to signs of hope, I describe some experiences and practices being used at the Methodist University of São Paulo, where we find similarities and possible connections with the material presented as the threads and the fabric of the network. I conclude this recovering and examining carefully points of the confluence between some aspects on the thoughts of the two authors as support of defense of what I consider the necessary education for the current historical moment, therefore, the one which I propose that should be developed by Methodist Educational Network.